Hak untuk Dilupakan sebagai Frontier of Justice: Analisis Peran Hakim dalam Mewujudkan Keadilan Digital - Andi Sitti Ainy Nur Alifah; Bulan, Indra (Ikatan Hakim Indonesia (IKAHI), 2025)
The presence of right to be forgotten is an essential starting point for protecting human dignity through the deletion, restrictions, or changing past records on internet. However, there are many challenges in the implementation of it which presents new limitations to the renewal of justice (frontier of justice). This study is going to answer how right to be forgotten is the frontier of justice and what is the role of judges in implementing right to be forgotten in order to realize digital justice. The urgency is to determine the role of judges in adapting to legal developments, such as determining the limits of justice for the existence of right to be forgotten. The method used is normative juridical with a literature review that will be concluded deductively. This study indicate that right to be forgotten is included in the frontier of justice because this right brings new boundaries in the process of seeking justice. These boundaries of justice arise because there is a clash in efforts to implement right to be forgotten with the implementation of other rights. Thus, judges through their decisions become the main pillar for implementing right to be forgotten. The role of judges is very crucial in maintaining human rights so that they are always balanced and do not cause conflict with other rights.